The association of co‐morbid insomnia and sleep apnea with prevalent cardiovascular disease and incident cardiovascular events. (15th February 2022) - Lechat, Bastien; Appleton, Sarah; Melaku, Yohannes Adama; Hansen, Kristy; McEvoy, R. Doug; Adams, Robert; Catcheside, Peter; Lack, Leon; Eckert, Danny J.; Sweetman, Alexander
Summary: Insomnia and obstructive sleep apnea commonly co‐occur (co‐morbid insomnia and sleep apnea), and their co‐occurrence has been associated with worse cardiometabolic and mental health. However, it remains unknown if people with co‐morbid insomnia and sleep apnea are at a heightened risk of incident cardiovascular events. This study used longitudinal data from the Sleep Heart Health Study ( N  = 5803) to investigate potential associations between co‐morbid insomnia and sleep apnea and cardiovascular disease prevalence at baseline and cardiovascular event incidence over ~11 years follow‐up. Insomnia was defined as self‐reported difficulties initiating and/or maintaining sleep AND daytime impairment. Obstructive sleep apnea was defined as an apnea–hypopnea index ≥ 15 events per hr sleep. Co‐morbid insomnia and sleep apnea was defined if both conditions were present. Data from 4160 participants were used for this analysis. The prevalence of no insomnia/obstructive sleep apnea, insomnia only, obstructive sleep apnea only and co‐morbid insomnia and sleep apnea was 53.2%, 3.1%, 39.9% and 1.9%, respectively. Co‐morbid insomnia and sleep apnea was associated with a 75% (odd ratios [95% confidence interval]; 1.75 [1.14, 2.67]) increase in likelihood of having cardiovascular disease at baseline after adjusting for pre‐specified confounders. In the unadjusted model, co‐morbid insomnia and sleep apnea was associated with a twofold increase (hazard ratio, 95% confidence interval: 2.00 [1.33, 2.99]) in risk of cardiovascular event incidence. However, after adjusting for pre‐specified covariates, co‐morbid insomnia and sleep apnea was not significantly associated with incident cardiovascular events (hazard ratio 1.38 [0.92, 2.07]). Comparable findings were obtained when an alternative definition of insomnia (difficulties initiating and/or maintaining sleep without daytime impairment) was used.